Method for preparation of fish feed from cow dung - CHEN YUN (2017)
The invention discloses a method for preparation of fish feed from cow dung. The method comprises the steps of: stacking, pile turning, feeding and mixing crushing. The treatment method provided by the invention is ecological, accords with the environmental protection requirements of sustainable development, and is low in treatment cost. Cow dung raises earthworms and is made into fish feed, thus generating additional economic benefits. 本发明公开了种采用牛粪制作鱼饲料的方法，包括以下步骤：架堆、翻堆、投喂和混合碾碎。本发明处理方法生态化，符合可持续发展的环保要求，且处理的成本低，通过牛粪养殖了蚯蚓并制作鱼饲料，产生额外的经济效益。